THE RATIONALE OF THE AXIOPSYCHOLOGICAL MODEL OF THE RESEARCH DIALOGUE IN MODERN PERSONOLOGY - Бондарєв, В. Л. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
There is an attempt of theoretical construction of the axiopsychological model of the research dialogue as a special case of intersubjective interaction with reflexive attitude to the current process and awareness of cognitive structures in the “Me – You” – “We – Univers”. It was found that elementary constructive criticism provokes interpretation generated therein reflection treatment shows that the understanding mechanism prepares and prints partners beyond the existing, changing the subjective characteristics of participants in the dialogue.